2021
DOI: 10.1039/d0sc05276k
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic resolution of racemic allylic alcohols via iridium-catalyzed asymmetric hydrogenation: scope, synthetic applications and insight into the origin of selectivity

Abstract: Asymmetric hydrogenation is one of the most commonly used tools in organic synthesis, whereas, kinetic resolution via asymmetric hydrogenation was less developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…In contrast to this strategy, Andersson reported the highly efficient kinetic resolution of a wide variety of allylic alcohols (Figure 13). 34 Critical to success was the addition of K 2 CO 3 to neutralize the generated Brønsted acid during the hydrogenation, eradicating epimerization of the starting material. The large difference in reactivity between the employed chiral iridium complex and both enantiomers of the allylic alcohols accounts for minimal consumption of the desired enantiomer with s-values up to 211.…”
Section: Development Of New Methodologymentioning
confidence: 99%
“…In contrast to this strategy, Andersson reported the highly efficient kinetic resolution of a wide variety of allylic alcohols (Figure 13). 34 Critical to success was the addition of K 2 CO 3 to neutralize the generated Brønsted acid during the hydrogenation, eradicating epimerization of the starting material. The large difference in reactivity between the employed chiral iridium complex and both enantiomers of the allylic alcohols accounts for minimal consumption of the desired enantiomer with s-values up to 211.…”
Section: Development Of New Methodologymentioning
confidence: 99%
“…In earlier investigations, the Ir-hydride species was found to be acidic, and in some cases, it has the capability to cleave the allylic alcohol C–O bond (Figure a) . Exploiting this acidic feature, an Ir-N,P-catalyzed hydrogenative DKR process was discovered and the mechanistic studies showed that the acid-assisted isomerization was the crucial element of the reaction (Figure a (2)) This reactivity pattern was also extended later to the deoxygenation of racemic alcohols to produce chiral alkanes (Figure a (3))…”
Section: Introductionmentioning
confidence: 93%
“…In this regard, asymmetric hydrogenation of allylic alcohols is a direct and efficient way to prepare chiral alcohols. Over the past few years, several works have been reported on the Ir-catalyzed hydrogenation of di-/tri-substituted primary/secondary allylic alcohols with excellent enantioselectivity . However, quaternary alcohols are for obvious reasons not directly accessible via asymmetric hydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetric hydrogenation is a direct and attractive route for transforming allylic alcohols into chiral alcohols, which are important building blocks for the synthesis of natural products and drugs. Despite the great progress made in the area of asymmetric hydrogenation, there are not many successful catalytic systems for asymmetric hydrogenation of allylic alcohols . The asymmetric hydrogenation of prochiral racemic secondary allylic alcohols to give a single enantioenriched product, which allows for accessing chiral alcohols with multiple stereogenic centers, is particularly challenging.…”
mentioning
confidence: 99%